Identification of a Peptide from Mammal Albumins Responsible for Enhanced Pigment Production by Group B Streptococci - Rosa-Fraile, Manuel (American Society for Microbiology, 1999)
The peptide from peptones responsible for enhanced pigment production by Streptococcus agalactiae in culture media has been isolated from a peptic digest of human albumin and has been identified as Ile-Ala-Arg-Arg-His-Pro-Tyr-Phe. The related heptapeptide lacking the N-terminal Ile also had pigment-enhancing activity. A sequence similarity search showed that these sequences are present only in mammal albumins.